PROFESSIONAL PRACTICE REPORT ON NEW PRODUCT DEVELOPMENT - Ozodbekova Azizakhon Pulatjon qizi (European Science Publishing, 2025)
The process of launching a new product on the market is called new product development. The application of this can be made to develop an entirely new product, enhance an existing one to maintain its attractiveness and competitiveness or introduce an old product to a new market. (Online, 2023).